When adaptive control fails: Slow recovery of reduced rapid online control during reaching under reversed vision. (May 2015) - Kuang, Shenbing; Gail, Alexander
Highlights: Reversed visual feedback induces sustained impairment in natural reach accuracy. Subjects show fast reduction of rapid online control of movements (ROC). Recovery of ROC with practice is slow, partial, and independent of visual feedback. Trial-by-trial adaptation of motor planning does not help to improve reach accuracy. Abstract: Previous studies have shown that short-term exposure to mirror-reversed visual feedback suppresses rapid online control (ROC) of arm movements in response to a sudden target displacement. Here we tested if the reduced ROC under reversed vision can be observed for natural reaches without target perturbations, i.e. without corrective movements that are driven by visual input perturbation. Second, we ask if such ROC reduction generalizes to movement phases without visual feedback of the hand. Subjects were instructed to perform simple reach movements towards a stationary target position either under normal or physically reversed vision of the hand during the late movement phase. We quantified time-resolved ROC via a coefficient of determination of the reach trajectories over the full course of the movement. As for other measures in previous studies, we found that our perturbation-independent ROC was reduced within a few trials after exposure to reversed visual feedback. The reduced ROC was restricted to late movement phases, and was not observed in early movement phases. We further asked if subjects would be able to re-gain ROC with prolonged exposure to the reversed visual input. ROC gradually and incompletely increased over the course of 400 exposure trials, affecting both early and late movement phases. Our results show that under reversed vision ROC is reduced even for perturbation-independent natural reaches aiming at stationary targets.